2009
DOI: 10.1111/j.1365-2028.2009.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effectiveness of contraception for controlling introduced populations of elephant in South Africa

Abstract: Re‐introduced African elephant (Loxodonta africana Blumenbach) populations are growing at very high rates in many of southern Africa’s reserves, have attained densities higher than previously thought possible and may be exhibiting irruptive growth. Active management of such populations is necessary to prevent the potentially negative effects on habitat and biodiversity that are associated with elephant overpopulation. One potentially feasible method of elephant management is immunocontraception, but very littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Female elephants may reach sexual maturity as late as 17 years [52] , and will typically produce the first calf two years later [55] , [56] , [57] . However, Mackey [11] , [58] calculated the average age of female sexual maturity in four small, enclosed reserves to be between 8 and 10 years. The average age of sexual maturity of the Munyawana population was previously thought to be 10 years [11] , but additional data up to 2009 indicate this to be nine years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Female elephants may reach sexual maturity as late as 17 years [52] , and will typically produce the first calf two years later [55] , [56] , [57] . However, Mackey [11] , [58] calculated the average age of female sexual maturity in four small, enclosed reserves to be between 8 and 10 years. The average age of sexual maturity of the Munyawana population was previously thought to be 10 years [11] , but additional data up to 2009 indicate this to be nine years.…”
Section: Methodsmentioning
confidence: 99%
“…The inter-calving interval of cows is between four and five years [55] , [59] , [60] , with estimates as high as four to nine years [61] . However, recent studies in enclosed populations in South Africa determined calving intervals at between three and four years [11] , [58] . Again, newer census data up to 2009 (but before immunocontraception took effect) for Munyawana indicate average calving interval has reduced from four years [11] to three years.…”
Section: Methodsmentioning
confidence: 99%
“…Hobbs et al [65], found that treating small populations -particularly those in enclosed protected areas -with lifetime contraception magnifies their extinction rate. Conversely, Mackey et al [71], opined that elephant contraception would only be effective on small populations in enclosed reserves, because their population age structures would be unstable enough for contraception to have an impact. In a large and old reserve like Kruger NP the elephant population is so large and stable that halting its growth rate would require sterilizing 75% of all females; and there are more than 7000 elephants in Kruger NP [52].…”
Section: Impacts On Population and Ecosystemmentioning
confidence: 99%
“…To help conserve elephants, Joyce Poole and colleagues make a number of conclusive comments, including the overall condemnation of ivory trade, sport hunting, and capture of wild elephants in any form. In contrast, an emerging question facing many managers of increasing elephant populations is how to reduce the risk of elephant overpopulation within protected areas (Mackey et al 2009). In the 2nd chapter, Harvey Croze and Keith Lindsay argue against the concept of elephant overpopulation in Amboseli, saying that managers should rather take a ''not-at-equilibrium'' ecological perspective.…”
mentioning
confidence: 97%